Brain-specific Crmp2 deletion leads to neuronal development deficits and behavioural impairments in mice - Hongsheng Zhang (Nature Portfolio, 2016)
The in vivo function of CRMP2 is unclear. Zhang et al. generate and characterize brain-specific Crmp2knockout mice. These mice show impairments in hippocampal neurogenesis, neuronal maturation and synaptic transmission, and exhibit schizophrenia-related behavioral deficits.